Multimedia Based Secre Coded Communication System - Shanmukanand Nandigam, Venkata Sai Anudeep Lingadahalli, Pavankumar N, Shashi Vardhan Reddy Peddakama, Sugandha Saxena (International Journal of Advanced Science and Technology, 2020)
This paper deals with the secure communication between the two entities using one of the Multimedia elements Text. Text communication is good when dealing with normal applications but in critical fields like Banking and Military there should not be any eavesdropping while sharing the information. In-order to overcome this problem different types of Cryptographic algorithms have evolved. Cryptography can be defined as converting the normal data into the non-understandable data. By using this technique secured system can be developed without the intervention of the third parties and providing the access to only the authorized users. This can be achieved using the state-of-the-art AES Algorithm (Advanced Encryption Standard). Till now AES is not used in this type of application because of its complexity in the implementation of the algorithm. To implement these complex algorithms controller should have the capability of both storing and running the complex algorithms. Raspberry Pi (Model- 3B) is one such controller which has the dual capability. The proposed system is designed to send the secure messages using the AES Algorithm for UHF (Ultra High Frequency) range using the Radio Frequency Modules (RF modules) comprises of RF Transmitter and the RF Receiver which uses ASK (Amplitude Shift Keying) technique for sending the text messages without using the internet.